Deployment and implementation of dynamic network policy in SDN - Ligang DONG; Bohan HE; Tijie XU; Shuocheng FEI; Weiming WANG (Dianxin kexue)
Software defined networking（SDN）provides a new solution for management requirements of the future network. Based on dynamic service function chain as the creation model of service function, advanced network programming language as a service deployment tools, and combined with virtual network mapping theory, a deployment scheme which could take services to policies, and take controllers to network nodes was designed. Based on the three-layer structure of the SDN, a dynamic policy management system was proposed. It can implement self-adaption deployment of network service, which based on the feedback information of the network state. Besides, it can detect network policy conflicts on the network note and choose different ways of combination to avoid policy conflicts. Finally, the complete deployment process of the dynamic policy management system was verified through some experiments.